Hobbes and Kant: Materialism and Rhetoric - Gonzalo Bustamante Kuschel (Problemos)
This article examines the subtle nuances of Hobbes’s and Kant’s perspectives on rhetoric and materialism, contextualising them within the broader framework of political philosophy. Despite both philosophers being critics of rhetoric, their approaches exhibit notable divergences. Hobbes, who advocated for monarchy, criticized rhetoric from the perspective of a materialist anthropology influenced by Lucretius. However, he paradoxically employed rhetorical strategies in his new scientia civilis. Despite critiquing both Lucretian materialism and rhetoric, Kant incorporated certain rhetorical elements compatible with his philosophical framework, particularly in relation to Epicureanism. This study analyses their interpretations of paradiastole and the implications for the political thought. The argument is that both thinkers, in seeking a rational foundation for the political order, anchor their notions of rationality in Epicurean materialism, by reconfiguring rhetorical elements to suit their respective philosophies. The article elucidates Kant’s republican proclivities and his aspiration to maximize the citizens’ autonomy, which contrasts with Hobbes’s monarchical orientation. This research contributes to a more nuanced understanding of the early modern political thought and its relevance to the contemporary republican and democratic theory.